Callogenesis and Plant Regeneration in Peony (Paeonia × suffruticosa) Using Flower Petal Explants - Xia Chen; Chengyang Ye; Hongmin Yang; Wen Ji; Zhen Xu; Sanchun Ye; Huasen Wang; Songheng Jin; Chao Yu; Xiangtao Zhu (Horticulturae, 2022)
Peony is a traditional Chinese flower with significant ornamental and medicinal value. However, there are still problems, such as serious browning, difficulties in differentiation, and rooting and low regeneration efficiency in the process of the regeneration system established, which have hindered the development of transgenic peony technology. Establishing an efficient regeneration system is considered to be an important goal among peony researchers. Here, we describe a protocol for high-frequency callus induction and establishment of peony plants using flower petals as explants. Murashige and Skoog (MS) medium supplemented with 2.0 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D), 1.5 mg/L N-(phenylmethyl)-9H-purin-6-amine (6-BA), and 0.3 mg/L 1-naphthylacetic acid (NAA) was identified as the best medium for callus induction, achieving an induction rate of up to 98.52%. The highest peony proliferation rate (234%) was achieved on MS supplemented with 0.2 mg/L NAA and 3.0 mg/L 6-BA. The highest callus differentiation rate (34.81%) was achieved on MS supplemented with 2.0 mg/L 6-BA and 0.5 mg/L zeatin (ZT). The highest rooting rate was 23.33% when using 1/2 MS supplemented with 0.1 mg/L NAA and 0.05 mg/L 3-indolebutyric acid (IBA). After acclimation, the plants were transferred to pots, where they showed robust growth. We also observed the surface structures of the calluses using scanning electron microscopy and found that the differentiation characteristics of the calluses were hugely variable and that different surface structures appeared to affect bud differentiation efficiency. The efficient and rapid system for regenerating peonies using petal cultures established here will create new opportunities for the mass reproduction and genetic engineering of peony plants.